High-resolution 3D demonstration of regional heterogeneity in the glymphatic system. Issue 11 (November 2022) - He, Xu-Zhong; Li, Xin; Li, Zhen-Hua; Meng, Jing-Cai; Mao, Rui-Ting; Zhang, Xue-Ke; Zhang, Rong-Ting; Huang, Huai-Liang; Gui, Qian; Xu, Guang-Yin; Wang, Lin-Hui
Accumulating evidence indicates that the glymphatic system has a critical role in maintaining brain homeostasis. However, the detailed anatomy of the glymphatic pathway is not well understood, mostly due to a lack of high spatial resolution 3D visualization. In this study, a fluorescence micro-optical sectioning tomography (fMOST) was used to characterize the glymphatic architecture in the mouse brain. At 30 and 120 min after intracisternal infusion with fluorescent dextran (Dex-3), lectin was injected to stain the cerebral vasculature. Using fMOST, a high-resolution 3D dataset of the brain-wide distribution of Dex-3 was acquired. Combined with fluorescence microscopy and microplate array, the heterogeneous glymphatic flow and the preferential irrigated regions were identified. These cerebral regions containing large-caliber penetrating arteries and/or adjacent to the subarachnoid space had more robust CSF flow compared to other regions. Moreover, the major glymphatic vessels for CSF influx and fluid efflux in the entire brain were shown in 3D. This study demonstrates the regional heterogeneity in the glymphatic system and provides an anatomical resource for further investigation of the glymphatic function.